Mathematical relationship between grid and low peclet numbers for the solution of convection-diffusion equation - Abdullah, Aslam (Asian Research Publishing Network (ARPN), 2018)
The problems of grid structure for the numerical calculations are heavily discussed in computational fluid dynamics. In this research, the importance of the relationships between the grid structure and the flow parameters in convection-diffusion problems is emphasized. In particular, we propose a systematic technique in setting the grid number based on its relationship with low Peclet number. Such linear mathematical connection between the two non-dimensional parameters serves as a guideline for a more structured decision-making and improves the heuristic process in the determination of the computational domain grid for the numerical solution of convection-diffusion equations especially in the prediction of the concentration of the scalar. The results confirm the effectiveness of the new approach.